IMPACT ASSESSMENT OF KONANKI WATERSHED PROJECT IN PRAKASAM DISTRICT ON BIO-PHYSICAL, ENVIRONMENTAL AND SOCIO-ECONOMIC ASPECTS - P. RANJIT BASHA, M. SIVA PRASAD, B. VENKATESULU NAIK, R. INIGO ARUL SELVAN and L. SUDHAKARA REDDY* (The Journal of Research ANGRAU, 2019)
Konanki mega watershed project was sanctioned in the year 2010-11 and implemented in Prakasam districttill March 2018. Impact study was conducted on environmental and socio-economic indicators by physical visit to theproject area and through bio-physical measurable characteristics by remote sensing and GIS techniques to assessthe outcomes and impact on the watershed community. The total geographical area of the project is 10,574 hahaving undulating terrain with net treatable area of 4,773 ha encompassing seven micro watersheds. The impact ofwatershed management interventions were observed in terms of sustaining the productivity of crops under droughtconditions, development of waste lands and current fallow lands, increase in cultivated area, improvement in agrivegetationand vigour, expansion of water bodies, soil moisture in the profile as a result of the effective in-situ soilconservation and water conservation activities, increase in milk productivity,etc. The water productivity also foundimproved through conservation measures and judicious use of available water resources. Watershed interventionshelped in enhancement of family income especially ofthe marginal farmers (37.1 % rise), small farmers (15% rise)and landless poor (76.1% rise) of watershed community.